Temporal and spatial distribution of stratospheric trace gases over Antarctica in August and September, 1987 - Coffey, M. T.; Mankin, William G. (1988)
There have been a large number of suggestions made concerning the origin of the Antarctic 'ozone hole' since its discovery; these changes include stratospheric chemistry, or changes in the solar input, or combinations of these effects. Supporting or refuting these theories requires a wide variety of data for comparison with the predictions. In Aug. and Sept., 1987, a field observation expedition was made over Antarctica from a base in Punta Arenas, Chile. Two aircraft, an ER-2 with in-situ instruments flew at altitudes up to 18 km measuring ozone, water, ClO, BrO, NO sub x, particles, and meteorological parameters in the ozone layer. A DC-8 flew at altitudes of 10 to 12 km, below the ozone layer, using remote sensing instruments for measuring composition and aerosol content of the ozone layer, as well as in-situ instruments for measuring composition at aircraft altitudes. The obsevation of a number of chemical species and their correlation with each other and with meteorological parameters gives a useful set of data for comparison with various theories.